(untitled) (Medico Legal Update, 2021)
Background: One of the most important agents that must be found in all dividing cells is folate. Aim: Assessment of human folate receptor-1 gene expression and correlation with leptin hormone in obese and non-obese subjectsof Babylon province, Iraq. Subjects and Method: This study included 60 obese subjects (OS) in the range of age (10-45 years) and 30 normal weight subjects (NOS) in range age of (11-43 years). FOR-1 gene expression were assessing by qRTPCR after RNA extraction from fresh blood of all obese and normal subjects and immediately converting into cDNA. Leptin was assessed by ELISA method. Results: The results suggesting that founds the positive correlation (r2 =0.447) between ages of OS and levels of LEP (ng/ml). The results of this study showed significant differences (p-value< 0.05) in levels of leptin (LEP) between OS and NOS groups. The results showing that the FOR-1 gene expression ratio in NOS compare to expression OS were 11.9 and 7.1. Conclusion: FOR-1 have a higher expression in OS compare to NOS and this may be useful in diagnostic and therapeutic tools in diseases or cancers in OS.